Staggered pillaring: a strategy to control layer–layer packing and enhance porosity in MOFs. Issue 11 (2nd July 2016) - Linder-Patton, Oliver M.; Doonan, Christian J.; Sumby, Christopher J.
Abstract: Convenient access to metal–organic frameworks (MOFs) with defined structural and chemical features is required to satisfy the design criteria for targeted applications. Here, we demonstrate that staggered pillaring between the layers of a binodal 2-D metal–organic framework (MOF) at only the alternating axial sites of the dimetallic copper(II) paddlewheel nodes aligns the 2-D layers and significantly increases the porosity of the resulting 3-D MOF. Two new pillared MOFs of this form were synthesized, [Cu3 (bcppm )2 (NO3 )2 (L)]·xS (wherebcppm  = bis(4-(4-carboxyphenyl)-1 H -pyrazolyl)methane and L = DABCO and pyrazine), via a mixed ligand synthesis. Both pillared 3-D frameworks have considerably larger BET surface areas than their 2-D counterpart, due to the alignment of 2-D layers from a staggered to eclipsed arrangement in the 3-D material; this increase in pore space and surface area is realized despite both materials being 2-fold interpenetrated. The strategy outlined here demonstrates a method of designing porous 3-D MOFs from nonporous 2-D-layered materials with a minimum of layer–layer connections. Abstract :